Effects of radiotherapy on central venous ports - Młynarski, Rafał; Gawron, Iwona; Przesmycki, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2007)
During radiotherapy of patients with implantable central venous ports we are often afraid of complications resulting from ports damage on the one hand and their interaction with surrounding tissues on the other hand. In experimental conditions venous ports were exposed to radiation. It was found that radiation reflected from a port is negligible and should not put patients at risk. Radiotherapy does not cause any changes within a port chamber, however it substantially affects elasticity of a polyurethane port catheter and to a minimal extent affects silicone catheter.